Challenges and Way Forward to Maintain Air Quality Standard in Urban Areas - Jena, Madhab C.; Mishra, Sarat K.; Moharana, Himanshu S. (The Global Environmental Engineers, 2023)
This thesis explores the intricate relationship between urban air pollution, economic growth, population dynamics, and energy consumption. Addressing impacts on climate change, biodiversity, agriculture, and human health, it emphasizes compromised urban air quality due to pollution sources such as power generation, vehicle traffic, and construction. Key pollutants like particulate matter, carbon dioxide, sulfur dioxide, and nitrogen dioxide pose significant health risks. The study identifies road transportation as a primary contributor, underlining alarming statistics from WHO on global air quality, particularly impacting low-level socio-economic regions. Legislations and policies dating back over a century form the foundation for global air pollution control efforts. The research highlights innovative solutions like urban green spaces, smart traffic management, and renewable energy investments. It stresses the importance of public transportation, electric vehicles, clean construction practices, and initiatives to reduce industrial emissions. In response to challenges, the thesis proposes a comprehensive mitigation plan covering strategy such as promoting public transport, energy conservation, recycling, and afforestation. It outlines a way forward, emphasizing integrated urban planning, public awareness campaigns, government policies, and international collaboration. In conclusion, the thesis calls for collective responsibility to address urban air pollution's adverse effects on public health and the environment. The proposed roadmap aims to create sustainable, resilient, and healthier urban environments through a holistic and collaborative approach.